2022
DOI: 10.1186/s13034-022-00535-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences, recent negative life events, and non-suicidal self-injury among Chinese college students: the protective role of self-efficacy

Abstract: Background Non-suicidal self-injury (NSSI) is a severe health problem closely related to adverse childhood experiences (ACEs). However, the underlying mechanisms by which ACEs may affect NSSI are largely unknown. Self-efficacy (NSSI-SE) and recent negative life events (RNLEs) may play important roles in this relationship. This study aimed to clarify the relationship between ACEs and NSSI among college students by examining the role of self-efficacy (NSSI-SE) and RNLEs in this process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…This is consistent with the findings of Chen et al, who showed a significant increase in NSSI behavior in individuals with high levels of childhood trauma. 27 This may be because when individuals encounter adverse experiences in childhood, they are not mature in cognition, thinking style, and personality characteristics, lack inner stability, and they are in a critical period of development, so individuals cannot acquire the ability to adapt and solve problems. This has also been confirmed by research that childhood adversity disrupts the ability to regulate or manage negative emotional states, leading to an increased risk of personal emotional problems and extreme distress.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of Chen et al, who showed a significant increase in NSSI behavior in individuals with high levels of childhood trauma. 27 This may be because when individuals encounter adverse experiences in childhood, they are not mature in cognition, thinking style, and personality characteristics, lack inner stability, and they are in a critical period of development, so individuals cannot acquire the ability to adapt and solve problems. This has also been confirmed by research that childhood adversity disrupts the ability to regulate or manage negative emotional states, leading to an increased risk of personal emotional problems and extreme distress.…”
Section: Discussionmentioning
confidence: 99%
“…We explored the association between MH, sex, NLEs, and NSSI and derived the following observations. First, patients with major depressive disorder and NSSI had experienced ACEs [ 35 , 37 , 47 ]. The present study clarifies the relationship between NLEs and NSSI and provides insights into how therapeutic interventions targeting NLEs can prevent the occurrence of NSSI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, patients with major depressive disorder and NSSI had experienced ACEs [ 35 , 37 , 47 ]. The present study clarifies the relationship between NLEs and NSSI and provides insights into how therapeutic interventions targeting NLEs can prevent the occurrence of NSSI [ 37 ]. Second, previous studies have established that NLEs and MH are associated with higher NSSI [ 14 , 17 ], and we observed an association between the two in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Siobhan O’Neill et al conducted a small sample sized study in UK (N = 739), and their results indicated a significant relationship between high levels of ACEs and NSSI ( 39 ). Chen et al showed that individuals with high levels of ACEs had significantly higher prevalence of NSSI among Chinese college students (N = 1,036) ( 40 ). The present study found significant accumulated effects of the number of ACEs on the odds of NSSI in the past 1 month, 6 months, and 12 months, extending the limited available evidence on the association between childhood adversities and NSSI.…”
Section: Discussionmentioning
confidence: 99%